A PET-based nomogram for oropharyngeal cancers. (April 2017) - Castelli, J.; Depeursinge, A.; Ndoh, V.; Prior, J.O.; Ozsahin, M.; Devillers, A.; Bouchaab, H.; Chajon, E.; de Crevoisier, R.; Scher, N.; Jegoux, F.; Laguerre, B.; et al.
Abstract: Purpose: In the context of locally advanced oropharyngeal cancer (LAOC) treated with definitive radiotherapy (RT) (combined with chemotherapy or cetuximab), the aims of this study were: (1) to identify PET-FDG parameters correlated with overall survival (OS) from a first cohort of patients; then (2) to compute a prognostic score; and (3) finally to validate this scoring system in a second independent cohort of patients. Materials and methods: A total of 76 consecutive patients (training cohort from Rennes) treated with chemoradiotherapy or RT with cetuximab for LAOC were used to build a predictive model of locoregional control (LRC) and OS based on PET-FDG parameters. After internal calibration and validation of this model, a nomogram and a scoring system were developed and tested in a validation cohort of 46 consecutive patients treated with definitive RT for LAOC in Lausanne. Results: In multivariate analysis, the metabolic tumour volume (MTV) of the primary tumour and the lymph nodes were independent predictive factors for LRC and OS. Internal calibration showed a very good adjustment between the predicted OS and the observed OS at 24 months. Using the predictive score, two risk groups were identified (median OS 42 versus 14 months, p < 0.001) and confirmed in the validation cohort from Lausanne (median OS not reached versus 26 months, p = 0.008 ). Conclusions: This is the first report of a PET-based nomogram in oropharyngeal cancer. Interestingly, it appeared stronger than the classical prognostic factors and was validated in independent cohorts markedly diverging in many aspects, which suggest that the observed signal was robust. Highlights: In locally advanced oropharyngeal cancers, recurrence occurs in up to 40% patients. PET allows a more accurate staging and may predict clinical outcome. In a first cohort, pretreatment PET parameters were analysed. A nomogram with a higher predictive value than classical parameters was generated. A validation was performed in a second cohort markedly diverging in many aspects.